Aldehyde dehydrogenase 2 activation ameliorates cyclophosphamide-induced acute cardiotoxicity via detoxification of toxic aldehydes and suppression of cardiac cell death. (August 2018) - Liu, Wenwen; Zhai, Xiaoxuan; Wang, Wenjun; Zheng, Boyuan; Zhang, Zhenxiao; Fan, Xinhui; Chen, Yuguo; Wang, Jiali
Abstract: Cyclophosphamide (CY)-induced acute cardiotoxicity is a common side effect which is dose dependent. It is reported that up to 20% of patients received high dose of CY treatment suffered from acute cardiac dysfunction. However, the effective intervention strategies and related mechanisms are still largely unknown. We aimed to investigate the effects of aldehyde dehydrogenase 2 (ALDH2), an important endogenous cardioprotective enzyme, on CY-induced acute cardiotoxicity and the underlying mechanisms. It was found that ALDH2 knockout (KO) mice were more sensitive to CY-induced acute cardiotoxicity, presenting as higher serum levels of creatine kinase-MB isoform and lactate dehydrogenase, and significantly reduced myocardial contractility compared with C57BL/6 (WT) mice. In addition, cardiac cell death, especially necrosis, was obviously increased in ALDH2 KO mice compared with WT mice after CY treatment. Furthermore, accumulation of toxic aldehydes such as acrolein and 4-HNE and reactive oxygen species (ROS) in the myocardium were significantly elevated after CY in ALDH2 KO mice. Importantly, ALDH2 activation by Alda-1 pretreatment markedly attenuated CY-induced accumulation of toxic aldehydes, cardiac cell death and cardiac dysfunction, without affecting CY's anti-tumor efficacy. In conclusion, the cardioprotective effects of ALDH2 activation against CY-induced acute cardiotoxicity are exerted via reducing toxic aldehydes accumulation and potentially interrupting the acrolein-ROS-aldehydes vicious circles, and thus alleviates myocardial cell death, without antagonizing the anti-tumor efficacy of CY. Therefore, ALDH2 might be a promising prevention and treatment target for CY-induced acute cardiotoxicity. Highlights: CY induced acute cardiac dysfunction and cell death, especially necrosis. ALDH2 KO mice were more sensitive to CY-induced acute cardiotoxicity. CY-induced acrolein-ROS-aldehydes vicious circles were blocked by Alda-1. Alda-1 ameliorated cardiotoxicity without antagonizing anti-tumor efficacy of CY.